Impossibility of adversarial self-testing and secure sampling - Akshay Bansal; Atul Singh Arora; Thomas Van Himbeeck; Jamie Sikora (Physical Review Research, 2024)
Self-testing is the task where spatially separated Alice and Bob cooperate to deduce the inner workings of untrusted quantum devices by interacting with them in a classical manner. We examine the task above where Alice and Bob do not trust each other which we call adversarial self-testing. We show that adversarial self-testing implies secure sampling—a simpler task that we introduce where distrustful Alice and Bob wish to sample from a joint probability distribution with the guarantee that an honest party's marginal is not biased. By extending impossibility results in two-party quantum cryptography, we give a simple proof that both of these tasks are impossible in all but trivial settings.